MAKSIMALISASI NILAI PERBANKAN SYARIAH MELALUI TEKNOLOGI PELAYANAN NASABAH TERKINI - Fani Firmansyah; Putri Kurnia Widiati (University of Merdeka Malang, 2016)
Sharia included in the companys development strategy which is needed by the Indonesian Bank. Banking business as high level of bussiness in competence for product and supply needs an effective development strategies to win the competition. The purpose of this study was to determine the development of technology, especially customer service associated with the financial capacity of Islamic Banking to meet the demand for these technologies in order to create added value for Islamic Banking and achieve an index of customer maximum satisfaction by using EVA analysis and analysis of the value of customer satisfaction for banking services. Results from this study is the customer wants maximum services such as guarantees for customer complain, the technological development of Islamic banking which is not rated maximally, and the develop-ment of the technology is still under conventional banking for Islamic Banking can not be maximized customer service technology, whereas the financial analysis of Islamic Banking is able to develop the technology.